Reelin levels in inflammatory bowel disease: A case-control study - Gencer, Selman; Can, Müçteba; Yüksel, İlhami (Journal of Surgery and Medicine, 2021)
Background/Aim: Crohn’s Disease (CD) and Ulcerative Colitis (UC) are grouped as Inflammatory Bowel Diseases (IBD). There are many similarities between these two diseases, and CD and UC cases cannot be separated at a rate varying between 5% and 10%. Reelin is an extracellular matrix protein first known for its vital role in neuronal migration. Studies in rodent small intestine suggested that reelin protects the organism from intestinal pathologies. In a 5-year retrospective case-control study, we aimed to detect the effectiveness of serum reelin level in patients with IBD in determining the severity and activation of the disease and compare healthy volunteers with patients in terms of inactivation and remission. Methods: The data of all 194 IBD patients diagnosed at Beyazit Training and Research Hospital between 2011-2015 were retrospectively reviewed. The patients were matched with 30 healthy volunteers. Risk factors were assessed by multivariate logistic regression analysis. Results: The serum reelin levels were similar between UC and CD patients, the control group, UC and CD groups (P=0.067), and those with active disease or disease in remission, and did not differ according to disease behavior or location of involvement. Conclusions: Our study shows that Reelin cannot be used as an activation/remission marker in IBD. In addition, it does not differentiate between UC and CD.